Legal Protection of Inheritance Rights for Children from Unregistered Polygamous Marriages A Comparative Analysis of Islamic Law and Indonesian Positive Law - Sofyan Munawar; Taufiq Ramadhan; Zaelia (Cv. Kayaswara, Indonesia, 2025)
The phenomenon of unregistered polygamous marriages has generated negative perceptions within society, particularly regarding justice in household relations. In practice, women and children born from unregistered marriages often lose their legal rights, such as maintenance and inheritance, due to the lack of state recognition of such marriages. Indonesian positive law, as regulated in Marriage Law No. 1 of 1974, requires marriage registration as the basis of legal validity; therefore, unregistered marriages do not provide formal legal protection. Meanwhile, from the perspective of Islamic law, an unregistered marriage is considered valid as long as it fulfills the pillars and requirements of marriage, thereby granting wives and children inheritance rights. This study aims to analyze the legal protection of inheritance rights for wives and children in unregistered polygamous marriages from the perspectives of Islamic law and positive law. The research employs a qualitative descriptive method with a normative juridical approach. Data were collected through observation, interviews with judges of the Religious Court and religious figures, as well as documentation from various legal sources. The results of the study indicate that: (1) under Islamic law, wives and children from unregistered polygamous marriages retain their legal status and inheritance rights as long as the marriage is religiously valid; (2) under positive law, the inheritance rights of wives and children from unregistered marriages are not recognized unless isbat nikah is conducted as a form of marriage legalization; and (3) mediation mechanisms and family deliberation serve as alternative means of resolving inheritance disputes; however, legal certainty ultimately requires official marriage registration and legalization.